The Impact of Executive Function on Emotional Dysregulation in Early Childhood: a Correlational Analysis - Restu Yuningsih; Meliana Sari; Wilma Rahmah Hidayati; Retno Wulandari; Jhoni Warmansyah (Universitas Nahdlatul Ulama Surabaya, 2024)
This study aims to evaluate the impact of early childhood executive function on emotional dysregulation. Participants were parents of children aged 5 to 6. Primary data was acquired by sending surveys via a Google Form. A correlational quantitative research approach was used. The research findings indicate that there is a relationship between executive function and emotional dysregulation in early childhood, particularly in Tanah Datar Regency. With a hypothesis test, the obtained value of r is 0.156, while the critical value (rtabel) for a sample size of 162 individuals is 0.148 at a significance level of 5%. The correlation test using SPSS 21 yields a significance value of 0.161, indicating a strong correlation between the two variables. The results showed that children's emotional dysregulation was highly influenced by their level of executive function in early childhood. This study emphasizes the need of recognizing and fostering executive function in early children to promote healthy emotional regulation, providing parents with vital insights into understanding and supporting their children's emotional development.